Escape to the Bayou - Williams, Amber Leigh (Harlequin romantic suspense, 2024)
Ten years ago, informant Javier Rivera helped free Dr. Grace LaCroix and her friends from human traffickers. When the leader of the cartel escapes and comes looking for vengeance, the traumatized surgeon must go on the run, again aided by Javier. Can she trust this man from her past? From the raucous streets of New Orleans's Mardi Gras to a ghostly plantation house deep in the bayou, Grace and Javier dodge the ruthless leader's attacks...until Grace's complicated feelings for her hero are threatened by the bombshell secret he keeps.